Prediksi Prestasi Mahasiswa dengan Jalur Siswa Berprestasi (PSB) Menggunakan Metode Naïve Bayers - Harwati -; Hanna Miratama (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
The purpose of this research is to predict the academic performance of students who submit university by special way (PSB) based on their GPA using naïve Bayes methods. The predicted results will be used to provide recommendations what attributes can be used as indicators of the selection through the PSB. From the calculation, it is resulted PSB students with satisfying GPA is they that have the attributes from Central Java, majoring in science, from public schools, parents' work of civil servants, have academic achievement during high school, and male. The level of accuracy for this calculation is equal to 51.69%.